INTERPERSONAL DYSFUNCTION PREDICTS SUBSEQUENT FINANCIAL EXPLOITATION VULNERABILITY IN OLDER ADULTS. (20th December 2022) - Han, Duke; Lim, Aaron; Mosqueda, Laura; Nguyen, Annie; Mason, Tyler; Weissberger, Gali; Fenton, Laura; Lichtenberg, Peter
Abstract: The goal of this study was to test whether interpersonal dysfunction, characterized by loneliness and/or dissatisfaction with relationships, is an imminent predictor of financial exploitation vulnerability (FEV) among older adults within a 6-month observation period. This study also tests whether FEV prospectively predicts interpersonal dysfunction. Twenty-six adults aged 50 or older completed a study involving baseline data collection and 13 follow-ups over 6 months. Linear mixed models were used for primary analyses. After adjustment for demographic, psychological, and cognitive covariates, there were between-person effects of FEV and interpersonal dysfunction across follow-ups, suggesting that those with generally higher interpersonal dysfunction compared to other participants also reported greater FEV (B(SE)=1.09(.33), p=.003). There was a within-person effect (B(SE)=.08(.03), p=.007) of elevated interpersonal dysfunction predicting greater FEV two weeks later across all follow-ups. Within-person effect of FEV was not predictive of interpersonal dysfunction (B(SE)=.25(.15), p=.10). Among older adults, individuals with higher interpersonal dysfunction relative to others in the study reported greater FEV throughout the 6-month observation period. Increased loneliness and social dissatisfaction, relative to one's average level, predicts subsequent increases in FEV, and may be an imminent risk factor for exploitation.